Viscosine as a Potent and Safe Antipyretic Agent Evaluated by Yeast-Induced Pyrexia Model and Molecular Docking Studies - Muhammad, Akhtar; Khan, Behramand; Iqbal, Zafar; Khan, Amir Zada; Khan, Inamullah; Khan, Kashif; Alamzeb, Muhammad; Ahmad, Nasir; Khan, Khalid; Lal Badshah, Syed; Ullah, Asad; Muhammad, Sayyar; et al. (American Chemical Society, 2019)
The antipyretic potential of viscosine, a natural product isolated from the medicinal plant Dodonaea viscosa, was investigated using yeast-induced pyrexia rat model, and its structure-activity relationship was investigated through molecular docking analyses with the target enzymes cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), and microsomal prostaglandin E synthase-1 (mPGES-1). The in vivo antipyretic experiments showed a progressive dose-dependent reduction in body temperatures of the hyperthermic test animals when injected with viscosine. Comparison of docking analyses with target enzymes showed strongest bonding interactions (binding energy -17.34 kcal/mol) of viscosine with the active-site pocket of mPGES-1. These findings suggest that viscosine shows antipyretic properties by reducing the concentration of prostaglandin E2 in brain through its mPGES-1 inhibitory action and make it a potential lead compound for developing effective and safer antipyretic drugs for treating fever and related pathological conditions. Copyright © 2019 American Chemical Society.